The evolution of the image of structure in the houses of Mies van der Rohe - Cervilla, Alejandro (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
Mies van der Rohe is considered one of the great masters of the twentieth century, both for the coherence of his work and for his ability to make modern architecture based on the importance of structure. This is recognized by the architect and architectural critic, Peter Blake, in the chapter he devoted to Mies van der Rohe, entitled "The Mastery of Structure", in his Masters of Architecture series. In the present article we would like to analyze the evolution of the image of structure in the houses of Mies van der Rohe, from his very first dwelling, Riehl House, built in Berlin in 1907, to his last house, Morris Greenwald, built in Weston in 1953. We will see how structure underwent a radical transformation over this period progressing from the innermost hidden realm of Architecture outwards to its exterior, and how in this process, the German maestro managed to transcend the idea of ​​structure and its load-bearing capability to convert it into the main artistic element of his architecture.
Keywords: Mies van der Rohe; Structure; Structural logic; Structural poetics